The 24-hour skin hydration and barrier function effects of a hyaluronic 1%, glycerin 5%, and Centella asiatica stem cells extract moisturizing fluid: an intra-subject, randomized, assessor-blinded study - Milani M; Sparavigna A (Dove Medical Press, 2017)
Massimo Milani,1 Adele Sparavigna2 1Difa Cooper, Caronno Pertusella, Varese, 2Dermatologic Institute Dermig Milan, Milan, Italy Introduction: Moisturizing products are commonly used to improve hydration in skin dryness conditions. However, some topical hydrating products could have negative effects on skin barrier function. In addition, hydrating effects of moisturizers are not commonly evaluated up to 24 hours after a single application. Hyaluronic acid (HA) and glycerin are very well-known substances able to improve skin hydration. Centella asiatica extract (CAE) could exert lenitive, anti-inflammatory and reepithelialization actions. Furthermore, CAE could inhibit hyaluronidase enzyme activity, therefore prolonging the effect of HA. A fluid containing HA 1%, glycerin 5% and stem cells CAE has been recently developed (Jaluronius CS [JCS] fluid). Study aim: To evaluate and compare the 24-hour effects of JCS fluid on skin hydration and on transepidermal water loss (TEWL) in healthy subjects in comparison with the control site. Subjects and methods: Twenty healthy women, mean age 40 years, were enrolled in an intra-subject (right vs left), randomized, assessor-blinded, controlled, 1-day trial. The primary end points were the skin hydration and TEWL, evaluated at the volar surface of the forearm and in standardized conditions (temperature- and humidity-controlled room: 23°C and 30% of humidity) using a corneometer and a vapometer device at baseline, 1, 8 and 24 hours after JCS fluid application. Measurements were performed by an operator blinded for the treatments. Results: Skin hydration after 24 hours was significantly higher (P=0.001; Mann–Whitney U test) in the JCS-treated area in comparison with the control site. JCS induced a significant (P=0.0001) increase in skin hydration at each evaluation time (+59% after 1 hour, +48% after 8 hours and +29% after 24 hours) in comparison with both baseline (P=0.0001) and non-treated control site (P=0.001). TEWL after 24 hours was significantly lower (P=0.049; Mann–Whitney U test) in the JCS-treated area in comparison with the control site (13±4 arbitrary units [AU] vs 16±6 AU). JCS fluid significantly reduced post-stripping TEWL in comparison with baseline after 1, 8 and 24 hours (–52%, –32% and –48%, respectively). In the control site, TEWL was not reduced in comparison with baseline values at each time point’s evaluation. Conclusion: A single application of JCS significantly improves skin hydration for up to 24 hours at the same time as improving skin barrier function. Keywords: moisturizing, hyaluronic acid, Centella asiatica stem cells, randomized controlled trial